Dual Anti-Inflammatory and Anti-Angiogenic Action of miR-15a in Diabetic Retinopathy - Wang, Qi; Navitskaya, Svetlana; Chakravarthy, Harshini; Huang, Chao; Kady, Nermin; Lydic, Todd A.; Chen, Y. Eugene; Yin, Ke-Jie; Powell, Folami Lamoke; Martin, Pamela M.; Grant, Maria B.; Busik, Julia V. (EBioMedicine, 2016)
Activation of pro-inflammatory and pro-angiogenic pathways in the retina and the bone marrow contributes to pathogenesis of diabetic retinopathy. We identified miR-15a as key regulator of both pro-inflammatory and pro-angiogenic pathways through direct binding and inhibition of the central enzyme in the sphingolipid metabolism, ASM, and the pro-angiogenic growth factor, VEGF-A. miR-15a was downregulated in diabetic retina and bone marrow cells. Over-expression of miR-15a downregulated, and inhibition of miR-15a upregulated ASM and VEGF-A expression in retinal cells. In addition to retinal effects, migration and retinal vascular repair function was impaired in miR-15a inhibitor-treated circulating angiogenic cells (CAC). Diabetic mice overexpressing miR-15a under Tie-2 promoter had normalized retinal permeability compared to wild type littermates. Importantly, miR-15a overexpression led to modulation toward nondiabetic levels, rather than complete inhibition of ASM and VEGF-A providing therapeutic effect without detrimental consequences of ASM and VEGF-A deficiencies.